W342F Mutation in CCaMK Enhances Its Affinity to Calmodulin But Compromises Its Role in Supporting Root Nodule Symbiosis in Medicago truncatula - Jauregui, Edgard; Du, Liqun; Gleason, Cynthia; Poovaiah, B. W. (Frontiers in Plant Science, 2017)
The calcium/calmodulin-dependent protein kinase (CCaMK) is regulated by free Ca2+ and Ca2+-loaded calmodulin. This dual binding is believed to be involved in its regulation and associated physiological functions, although direct experimental evidence for this is lacking. Here we document that site-directed mutations in the calmodulin-binding domain of CCaMK alters its binding capacity to calmodulin, providing an effective approach to study how calmodulin regulates CCaMK in terms of kinase activity and regulation of rhizobial symbiosis in Medicago truncatula. We observed that mutating the tryptophan at position 342 to phenylalanine (W342F) markedly increased the calmodulin-binding capability of the mutant. The mutant CCaMK underwent autophosphorylation and catalyzed substrate phosphorylation in the absence of calcium and calmodulin. When the mutant W342F was expressed in ccamk-1 roots, the transgenic roots exhibited an altered nodulation phenotype. These results indicate that altering the calmodulin-binding domain of CCaMK could generate a constitutively activated kinase with a negative role in the physiological function of CCaMK.